2004
DOI: 10.1002/macp.200400188
|View full text |Cite
|
Sign up to set email alerts
|

High‐Molecular‐Weight Isobutene–Isoprene Copolymers Containing Unusually High Isoprene Content

Abstract: Summary: The 1:2 adduct of the highly electrophilic borane B(C6F5)3 with n‐decanoic (stearic) acid, [n‐C17H35CO2H][B(C6F5)3]2 exhibits sufficiently enhanced acidity that it is an excellent initiator for the carbocationic copolymerization of isobutene with isoprene in methylene chloride and methyl chloride. High conversions to gel free, high‐molecular‐weight copolymers containing up to 15 wt.‐% isoprene are readily obtained, consistent with the anion [n‐C17H35CO2{BC6F5)3}2]− being very weakly coordinating. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Besides, T g values of IIR and BIIR were estimate sketchy by using Sythia module in MS. Figure suggests that the increasing isoprene (or SABI) content in IIR (or BIIR) results in a rise of T g , which is in accordance with the work reported by McInenly . Moreover, it shows that the SABI unit exerted a more significant impact than the isoprene unit on T g .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Besides, T g values of IIR and BIIR were estimate sketchy by using Sythia module in MS. Figure suggests that the increasing isoprene (or SABI) content in IIR (or BIIR) results in a rise of T g , which is in accordance with the work reported by McInenly . Moreover, it shows that the SABI unit exerted a more significant impact than the isoprene unit on T g .…”
Section: Resultssupporting
confidence: 89%
“…It was reported that the low‐level unsaturated units between long polyisobutylene segments will bring about the excellent gas barrier and good flex properties of BIIR . However, only a few experimental studies on altering the copolymer composition of IIR rather than BIIR have been reported . For example, Garratt et al developed an initiating system for preparing IIR with high isoprene content and confirmed the high efficiency of the system .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from Figure 7, the high frequency resonances at 1.108 ppm and 1.412 ppm were attributed to the methyl proton and methylene proton of the polyisobutylene units of butyl rubber 24, 30. Because of the low unsaturation, the weak frequency resonances in the region of 1.50–2.20 ppm were assigned to the isoprenyl units.…”
Section: Resultsmentioning
confidence: 96%
“…Polyisobutylene (PIB) based materials are widely used commercially in a variety of products, such as automobile tires, sporting equipment, adhesive sealants, viscosity modifiers, chewing gums and drug eluting stents . The widespread use of these polymers can be attributed to their favorable properties, including exceptional thermal and chemical stability, impermeability to gas and water, high damping and high elasticity.…”
Section: Introductionmentioning
confidence: 99%